Bimetallic Reactivities of Dinuclear Iridium and Rhodium Complexes Generated from Two Types of Alkyne‐Containing Bisphosphine Ligands. Issue 19 (12th May 2020) - Sasakura, Kohei; Okamoto, Kazuhiro; Ohe, Kouichi
Abstract : We have investigated the reactivities of a series of dinuclear iridium(II, II) and rhodium(II, II) 1, 3‐butadiene‐1, 4‐diyl complexes derived from two types of alkyne‐containing ligands. Newly developed ligand 2 afforded 2nd generation diiridium complexes that have higher reactivity toward halide substitution and acetylide formation. The significant differences in reactivity, influenced by the 1, 3‐butadiene‐1, 4‐diyl ligand backbone of these complexes, have been systematically investigated by synthetic studies as well as X‐ray crystallographic and spectroscopic analyses. Abstract : Reactivities of dinuclear iridium(II, II) and rhodium(II, II) 1, 3‐butadiene‐1, 4‐diyl complexes derived from P‐alkyne‐P ligands have been demonstrated. 2 nd generation diiridium complexes derived from newly developed P‐alkyne‐P ligand having the elongated linker exhibited higher reactivity toward halide substitution, ligand exchange, and acetylide formation. X‐ray crystallography and DFT calculations elucidate the metal–metal and metal–ligand interactions.